2004
DOI: 10.1074/jbc.m311625200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ Ligands Regulate Myeloperoxidase Expression in Macrophages by an Estrogen-dependent Mechanism Involving the -463GA Promoter Polymorphism

Abstract: A functional myeloperoxidase (MPO) promoter polymorphism, ؊463GA, has been associated with incidence or severity of inflammatory diseases, including atherosclerosis and Alzheimer's disease, and some cancers. The polymorphism is within an Alu element encoding four hexamer repeats recognized by nuclear receptors (AluRRE). Here we show that peroxisome proliferatoractivated receptor ␥ (PPAR␥) agonists strongly regulate MPO gene expression through the AluRRE. Opposite effects were observed in granulocyte/macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 68 publications
6
106
2
2
Order By: Relevance
“…Elevated serum MPO is an indicator for heightened risk of coronary artery disease (CAD) events [19,20], while individuals with inherited MPO deficiencies have reduced cardiovascular disease [21]. Members of the nuclear receptor superfamily, notably PPARγ and estrogen receptor, have been found to play key roles in regulating human MPO gene expression [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum MPO is an indicator for heightened risk of coronary artery disease (CAD) events [19,20], while individuals with inherited MPO deficiencies have reduced cardiovascular disease [21]. Members of the nuclear receptor superfamily, notably PPARγ and estrogen receptor, have been found to play key roles in regulating human MPO gene expression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A functional MPO promoter polymorphism, −463 G/A, alters expression levels [12,13], and is associated with increased incidence of CAD [14][15][16] and severity of atherosclerosis [17,18]. Elevated serum MPO is an indicator for heightened risk of coronary artery disease (CAD) events [19,20], while individuals with inherited MPO deficiencies have reduced cardiovascular disease [21].…”
Section: Introductionmentioning
confidence: 99%
“…This cluster is recognized by various nuclear receptors (Piedrafita et al 1996;Vansant and Reynolds 1995): c.-653G in the first hexamer creates an SP1 site, whereas c.-653A creates a binding site for the estrogen receptor a (ER-a). This raises the possibility that the estrogen receptor may contribute to differential regulation of MPO among G and A allele carriers in men and women, as reported in numerous studies (Kumar et al 2004;Reynolds et al 2000;Norris et al 1995). In this regard, we analyzed the effects of the MPO c.-653G [ A polymorphism on LDL characteristics separately in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kumar et al (Kumar et al 2004) demonstrated that gender differences in MPO c.-653G [ A polymorphism association are not caused by a direct impact of estrogen receptor binding on the MPO promoter. Indeed, PPARG heterodimerizes with retinoid X receptor (RXR) to bind two direct MPO hexamers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation